LEGAL INTEGRATION AS A MEANS TO REGIONAL ECONOMIC INTEGRATION: A SOUTHERN AFRICAN PERSPECTIVE - Kawenda, Diana Eunice (Indonesian Journal of International Law, 2016)
It is a general truth that regional integration has been considered as a means to achieve rapid economic growth and alleviate other socio economic ills faced in Southern Africa. In Southern Africa a lot of information has been expounded from an economist and political perspective on how regional integration cane be achieved. However not much emphasis has been placed on the role of the law in realising regional integration. This paper seeks to define the concept of regional integration and legal integration in International law considering the two concepts deal with interstate relations. Undoubtedly the most successful economic integration process has been fulfilled by the European Continent. In trying to ascertain if legal integration can be a means to achieve regional integration, the European Economic Community (EEC) will be examined. The role of the European Court of Justice (ECJ) will be discussed along with the landmark cases which set the law as the precursor to Europe’s successful integration process. A continental shift will be made to assess if the African Union (AU) considers the law as a means to effective regional integration. Moving further inward in the African continent, this paper will examine the position of the Southern African Development Community (SADC) and the Common Market for East and Southern Africa (COMESA), and if the law is being used as a means to effective regional integration? Lastly recommendations will be made pertaining to the African scenario and particularly in Southern Africa thus leading to the conclusion. The research methods used for this paper will be a comparative analysis with the European Integration process, literature review and internet research.